Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am to solve the equation $z^2 - (3-4i)z + (2-4i) = 0$, and also have to help me that $w^2 = -\frac{15}{4} - 2i$.

I can ofcourse find $w$, but I fail to see how this helps me in solving $z^2 - (3-4i)z + (2-4i) = 0$. What am I missing? Is there a connection I fail to see?

share|cite|improve this question
Try completing the square. – Hans Lundmark Sep 13 '12 at 9:23
up vote 3 down vote accepted

$z=\frac{3-4i±\sqrt{(3-4i)^2-4\cdot 1\cdot (2-4i)}}{2}$

Now, $(3-4i)^2-4\cdot 1\cdot (2-4i)=-15-16i=1^2+(4i)^2-2\cdot 1\cdot 4i=(1-4i)^2$

So, $z=\frac{3-4i±(1-4i)}{2}=1$ or $2-4i$

$4w^2=-15-8i=(1)^2+(4i)^2-2\cdot 1\cdot 4i=(1-4i)^2$


Alternatively, let $-\frac{15}{4}-2i=(a-ib)^2$

So, $-\frac{15}{4}-2i=a^2-b^2-i2ab$

$a^2-b^2=-\frac{15}{4}$ and $2ab=2$




So,$a=±\frac{1}{2},b=±2$ as $a,b$ are of same sign.

The square root of $(3-4i)^2-4\cdot 1\cdot (2-4i)=-15-16i$ can be calculated in the same way.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.